2002
DOI: 10.1002/1521-4141(200208)32:8<2365::aid-immu2365>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ T cells as immunoregulatory T cells in vitro

Abstract: We have further characterized the in vitro phenotype and function of anergic and suppressive CD4+25+ T cells. Following TCR ligation, DO.11.10 CD4+25+ T cells suppress the activation of OT‐1 CD8+25– T cells in an antigen nonspecific manner. Although suppression was seen when using a mixture of APC from both parental strains, it was very much more marked when using F1 APC. APC pretreated with, and then separated from CD4+25+ T cells did not have diminished T cell costimulatory function, suggesting that APC are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…In DO11.10 mice, 4 -6% of CD4 ϩ T cells constitutively express CD25, which was consistent with previous findings (25,34). Our analysis revealed that the majority of CD4 ϩ CD25 ϩ T cells in these animals express the transgenic TCR as defined by staining with the KJ1-26 Ab.…”
Section: Discussionsupporting
confidence: 92%
“…In DO11.10 mice, 4 -6% of CD4 ϩ T cells constitutively express CD25, which was consistent with previous findings (25,34). Our analysis revealed that the majority of CD4 ϩ CD25 ϩ T cells in these animals express the transgenic TCR as defined by staining with the KJ1-26 Ab.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, a plausible explanation for the lack of AICD in Tregs is diminished or absent CD95L expression. However, contradictory results regarding CD95L expression by Tregs have been obtained (16,(25)(26)(27)) that prompted us to investigate CD95L surface protein expression in Tregs compared with that in Tcons by a highly sensitive flow cytometry protocol. Tcons displayed high CD95L surface protein upon stimulation for 20 h with anti-CD3 Ab on day 6 of in vitro culture and upon P/I treatment on both day 0 (freshly isolated) and day 6 of culture ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-CTLA-4 does not, however, successfully reverse in vitro suppression in all studies (Chai et al, 2002;Thornton and Shevach, 1998). Studies with human cultured cells have suggested that CTLA-4 blockade has only a moderate or no effect on the suppressive function of CD4 + CD25 + regulatory T cells (Annunziato et al, 2002;Levings et al, 2001b).…”
Section: Ctla-4 As a Non Cell-autonomous Regulator: Regulatory T Cellmentioning
confidence: 98%